THE MILITARY CAPACITY OF THE ARMED FORCES AND THE FUNDAMENTAL RIGHTS OF PEOPLE IN THE CONTEXT OF THE RESPONSE TO COVID-19 - Diez Mayrena, Jose Carlos (2021)
The pandemic generated by COVID-19 constitutes a threat to the security and defense of a State, therefore, it must be countered based on the participation of all government institutions, in order to safeguard the well-being of the population and control the execution of the measures imposed to prevent the advance of the virus. In this sense, the objective of this research was to analyze the relationship between the military capacity of the Armed Forces and respect for the fundamental rights of the person in the national emergency caused by Covid-19, in the Lima Region. The research was descriptive-correlational and quantitative approach; while the design was non-experimental and cross-sectional, supported by the hypothetico-deductive model. The population was made up of active officers of the Armed Forces, and the non-probabilistic sample was made up of 368 officers of the Armed Forces, to whom observation and survey techniques were applied, this last instrument was the Likert-style questionnaire composed of 22 items, applied to the selected sample. It was concluded that the military capacity currently available to the Armed Forces of Peru, although they made it possible to fulfill the assigned mission within the framework of respect for Fundamental Rights, requires an increase in the budget and investment of the State, so that they can comply with the assigned strategic roles, having as a legal framework the unrestricted respect of the fundamental rights of its citizens.